Development of Interactive Media Integrated with Local Wisdom to Enhance Students’ Concept Mastery and Creative Thinking - Dunia Purnama; Dini Annisha; Berti Yolida; Hermansyah Hermansyah (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
The integration of local wisdom into learning media is considered to make science lessons more contextual, engaging, and meaningful for students. This study aims to develop and assess an interactive learning medium that integrates local wisdom, based on the traditional game begasingan, to enhance students’ conceptual understanding and creative thinking in science learning, particularly in the context of force and motion. The research used a 4D development model (Define, Design, Develop, Disseminate) involving expert validation, practicality testing with teachers and students, and effectiveness evaluation through a quasi-experimental design. The sample consisted of 60 junior high school students, divided into an experimental and a control group. The media was validated with high results (Aiken’s V = 0.83–0.92), considered highly practical by teachers (92.6%) and students (89.4%). The experimental group achieved higher NGain scores (0.68) than the control group (0.44), indicating better concept mastery. Creative thinking skills, including fluency, flexibility, and originality, also improved significantly in the experimental group. The results suggest that integrating cultural elements into interactive media effectively supports contextual science learning while preserving local identity.